2021
DOI: 10.1186/s13223-021-00577-8
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ Tregs ameliorate inflammatory reactions in a murine model of allergic rhinitis

Abstract: Background CD8+CD25+fork-head box transcription factor (Foxp3)+ regulatory T cells (CD8+ Tregs) play a role in immune tolerance. However, the role of these cells in allergic rhinitis (AR) has not been elucidated. The study aimed to evaluate influences of CD8+ Tregs on inflammatory conditions in a murine model of AR. Methods A murine model of AR was established. CD8+ Tregs were isolated from mice nasal mucosa and cultured in vitro. We examined inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…On the other hand, TGF-β is critical for the development and differentiation of Treg [ 137 ]. The effect of TGF-β on immune tolerance was studied by Lin et al, who assessed the role of Treg cells in the context of AR [ 138 ]. Their study showed that the adoptive transfer of AR CD8 + Treg increased the levels of TGF-β in mice nasal lavage fluids, which was associated with a reduced number of sneezes and nasal rubbing incidents in the treated animals.…”
Section: Micro-immunotherapy and 2lalerg ® : The U...mentioning
confidence: 99%
“…On the other hand, TGF-β is critical for the development and differentiation of Treg [ 137 ]. The effect of TGF-β on immune tolerance was studied by Lin et al, who assessed the role of Treg cells in the context of AR [ 138 ]. Their study showed that the adoptive transfer of AR CD8 + Treg increased the levels of TGF-β in mice nasal lavage fluids, which was associated with a reduced number of sneezes and nasal rubbing incidents in the treated animals.…”
Section: Micro-immunotherapy and 2lalerg ® : The U...mentioning
confidence: 99%
“…Certain research has indicated that, under chronic stimulation or specific pathological conditions, such as chronic infections or cancer, CD8+ T cells may experience immune exhaustion, characterized by a gradual loss of function and activity in response to sustained stimuli (41). Regulatory CD8+ T cells have inhibitory effects during AR occurrences, impacting inflammatory responses (42)(43)(44). Though not primary participants in allergic reactions, CD8+ T cells may exhibit exhaustion in response to allergens.…”
Section: Discussionmentioning
confidence: 99%
“…This population is poorly studied and is usually a heterogeneous group [70, 71]. Since CD8 + T cells bind to MHC-I, CD8 + regulatory T lymphocytes are more studied in transplantation mouse models in comparison to food allergy, however some studies report that CD8 + CD25 + Foxp3 + T cells can ameliorate inflammatory responses in allergic diseases [71, 72]. These TGF-ß expressing regulatory T cells are crucial for the induction and maintenance of oral tolerance together with CD4 + regulatory T cells [73].…”
Section: Discussionmentioning
confidence: 99%